Complex truth from simple beauty: Oscar Wilde’s philosophy of art - Lynch, Liam Joseph (Curtin University, 2014)
In this thesis I analyse a selection of the works of playwright, poet, novelist and essayist, Oscar Wilde, with the purpose of interpreting his philosophy of art. The thesis interprets Wilde’s philosophy of art as embodying a dialectical relationship, in the Hegelian sense, between the aesthetic, sensual experience of art, and the cognitive contemplation of the artwork.